Phycotoxins : (Blackwell Pub, 2007)
Phycotoxins: Chemistry and Biochemistry presents the most updated information available on phycotoxins. Major emphases are given to chemistry and biochemistry, while minor emphases are given to the aspects of origin, toxicology, or analytical methodology. The book discusses 16 phycotoxins, 7 on those affecting the nervous systems, 4 affecting other body systems; and 4 with undefined targets. The detailed information on chemistry in Phycotoxins: Chemistry and Biochemistry provides investigators, regulators, food technologists and toxicologists an updated basis on which research in other areas such as toxicology, mechanism of action, analytical methodology and pharmacology can be successfully developed and expanded.